Effects of Social Counseling on Parents of a Child With Cancer. (July 2020) - Haunberger, Sigrid; Rüegger, Cornelia; Baumgartner, Edgar
When a child is diagnosed with cancer, there can be serious consequences for the entire family. The purpose of this study was to explore the relationship between social counseling based on different social diagnostic methods and parent's quality of life, psychosocial burden, and sense of coherence. Seventy-one parents of children with cancer were randomly assigned to the intervention and control groups and were interviewed at three measurement times. Analysis of covariance was used for the data analysis. With respect to the effects of social counseling based on different social diagnostic methods, the results are somewhat mixed. We found only few significant effects between the intervention and control groups but a significant influence of moderating variables like the child's health status. There were significant changes in parent's quality of life and psychosocial burden, but the findings provided no evidence that one social diagnostic method works better than the other one. Methodological reasons concerning sample size and program integrity are discussed.